The effects of i-Think graphic organizers on reading comprehension of primary schools students in Seremban, Negeri Sembilan - Liow, Choy Yoke; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The current research investigates how i-Think graphic organizers impacts on reading comprehension of primary school students. Participants were purposively assigned to aged 9 to aged 11 primary schools’ students. The sample of this study was 264 primary schools students. This study was lasted for four weeks. Data were gathered through a questionnaire was analyzed quantitatively to indicate impact of i-Think graphic organizers in students’ reading comprehension. The results suggest that i-Think graphic organizers can be effective apply in reading comprehension of learners of English as a second language.